On low-dimensional filiform leibniz algebras and their invariants. - Sattarovich, Rakhimov Isamiddin; Hassan, Munther A. (Cornell University Library, 2011)
The paper deals with the complete classification of a subclass of complex filiform Leibniz algebras in dimensions 5 and 6. This subclass arises from the naturally graded filiform Lie algebras. We give a complete list of algebras. In parametric families cases, the corresponding orbit functions (invariants) are given. In discrete orbits case, we show a representative of the orbits.